Pemanfaatan Aplikasi Canva Sebagai Media Pembelajaran pada Siswa MA Daar Al-ilmi - Elis Sulistia; Muhammad Syifa Alfatih; Asriyudi Nur Imansya; Novi Yendra (Pusat Riset dan Inovasi Nasional, 2024)
The utilization of technology in education has become crucial in enhancing the effectiveness of learning. One platform that can be utilized is Canva, a user-friendly graphic design tool widely used by users in various fields. This research aims to examine the potential utilization of Canva as a learning resource for students in Islamic boarding schools (pesantren). The methods employed include literature review and direct observation in related pesantren. The results of community service show that Canva can be effectively used as a means to create visually engaging and interactive learning materials. In its development, a clear problem-solving framework, involvement of relevant target groups, and evaluation of results and discussions are required. In conclusion, the utilization of Canva in learning at pesantren can enhance students' motivation and interest, provide variation in the use of learning resources, and facilitate accessibility of learning materials. Further suggestions include conducting more studies on the effectiveness of Canva usage in pesantren learning and developing more specific guidelines for educational purposes.